The Influence of Artificial Intelligence in Development of Far Right in Europe - Febi Rosseva Amalinda; Saptatia Drajati Nugrahani, Henny (International Journal of Educational Research & Social Sciences, 2024)
The study aims to analyse the use of AI on social media by non-state far-right activists and   actors in Europe in the political year 2022-2023. The study also examines the problems posed by the use of AI in a political context and the legal measures implemented by European countries to mitigate these potential risks. Far-right ideology is not a new ideology in Europe. This ideology has existed since the 18th century. In the 2022-2023 political year, far-right parties gained seats in parliament and won elections in several European countries. This research is qualitative research using a critical paradigm. This research uses the Theory of Public Sphere. This theory was put forward by Jürgen Habermas whose essence is the formation of group opinion that can maintain structure, modify structure and ideological goals can be resistance to the practice of government and power. Public space theory also analyses the influence of AI in helping to promote the spread of extremist narratives, broaden the appeal of far-right movements to society, and create an atmosphere that encourages radicalization. The results of this study show how important it is to understand how AI technology interacts with the political dynamics of extremism in Europe.